Human Resource Development to Support the Implementation of the Medical Cannabis Policy in Thailand - พัฒนะวาณิชนันท์ ณัฏฐญา; ลิ้มสวาท วิรุฬ; วิเศษพลชัย บุษบงก์; สุขสุทธิ์ ปารณัฐ (Journal of Health Science of Thailand, 2020)
This qualitative research aimed to explore the context and factors of hospitals’ readiness for the implementation of the medical cannabis policy, and to identify the ways for human resource development to support the implementation. It was conducted from February to April 2020 using anthropological ethnographic methods utilizing multiple theories, including the main one from implementation science. The study samples were the eight pilot hospitals of the Ministry of Public Health that started providing medical cannabis service in August 2019. The results were analyzed and organized into three main aspects of the policy implementation: (1) the overall policy analysis, (2) the analysis of the system of policy implementation, and (3) the analysis of the hospitals’ readiness. The results showed that the medical cannabis policy in Thailand was a health policy that was the result of not only the political requirement and enforcement of the cabinet and the Minister of Public Health, but also the needs of the Thai people. Because of the cultural context of this policy, the success of policy implementation depended primarily on the support from the health workforce. Therefore, human resource development should be focused on both the direct development of the workforce and the improvement of the work system. These ways would enhance the workforce’s motivation, which is the core component of the readiness of the hospitals to support the success of the implementation of the policy.